Regulator of Calcineurin 1 helps coordinate whole‐body metabolism and thermogenesis. (2nd November 2018) - Rotter, David; Peiris, Heshan; Grinsfelder, D Bennett; Martin, Alyce M; Burchfield, Jana; Parra, Valentina; Hull, Christi; Morales, Cyndi R; Jessup, Claire F; Matusica, Dusan; Parks, Brian W; Lusis, Aldons J; et al.
Abstract: Increasing non‐shivering thermogenesis (NST), which expends calories as heat rather than storing them as fat, is championed as an effective way to combat obesity and metabolic disease. Innate mechanisms constraining the capacity for NST present a fundamental limitation to this approach, yet are not well understood. Here, we provide evidence that Regulator of Calcineurin 1 ( RCAN1 ), a feedback inhibitor of the calcium‐activated protein phosphatase calcineurin (CN), acts to suppress two distinctly different mechanisms of non‐shivering thermogenesis (NST): one involving the activation of UCP1 expression in white adipose tissue, the other mediated by sarcolipin (SLN) in skeletal muscle. UCP1 generates heat at the expense of reducing ATP production, whereas SLN increases ATP consumption to generate heat. Gene expression profiles demonstrate a high correlation between Rcan1 expression and metabolic syndrome. On an evolutionary timescale, in the context of limited food resources, systemic suppression of prolonged NST by RCAN1 might have been beneficial; however, in the face of caloric abundance, RCAN1‐mediated suppression of these adaptive avenues of energy expenditure may now contribute to the growing epidemic of obesity. Synopsis: Regulator of Calcineurin1 (RCAN1) suppresses two different mechanisms of non‐shivering thermogenesis: the activation of UCP1 expression in white adipose tissue, and sarcolipin expression in skeletal muscle. Mice deficient for Rcan1 have an elevated metabolic rate and are resistant to diet‐induced obesity. Tissue‐specific gene expression profiles from inbred mouse strains demonstrate a high correlation between Rcan1 expression in adipose and metabolic syndrome. The RCAN1 gene is located on chromosome 21 in humans. These findings may provide insights into the challenges of weight regulation in individuals with Down syndrome. Abstract : Regulator of Calcineurin1 (RCAN1) suppresses two different mechanisms of non‐shivering thermogenesis: the activation of UCP1 expression in white adipose tissue, and sarcolipin expression in skeletal muscle.